Different Gelatins Used in the Encapsulation of Fish Oil (Asian Journal of Pharmaceutics (AJP), 2024)
Fish oil, containing omega-3 polyunsaturated fatty acids such as eicosapentaenoic acid and docosahexaenoicacid, has attracted considerable interest for its health advantages, such as reducing inflammation and decreasingtriglyceride levels. Nonetheless, fish oil is highly susceptible to oxidation, resulting in rancidity, reducedeffectiveness, and unwanted smells, creating difficulties in its application as a dietary supplement. Using gelatin,encapsulation is commonly used to safeguard fish oil from oxidation and enhance its stability. This methodinvolves enveloping the oil in a biopolymer to create a shield that guards against elements such as oxygen andlight. Gelatin, obtained from different animal origins, is important in encapsulation. Various forms of gelatin, suchas porcine skin gelatin (PSG), bovine skin gelatin (BSG), and fish gelatin (FG), have different characteristics thatimpact encapsulation efficiency and the stability of the enclosed fish oil. PSG and BSG are well-liked becausethey are readily accessible, cost-efficient, and have outstanding gel-forming capabilities. Nevertheless, their usemay be restricted in specific markets due to dietary and religious guidelines. FG, obtained from fish skin andbones, is a better option that meets these limitations and fits well with human biology. A thorough search plan wascreated to locate pertinent papers from electronic databases such as PubMed, Google Scholar, Web of Science,or Scopus. This review examines the utilization of various kinds of gelatin to encapsulate fish oil, studying howtheir physical and chemical properties disturb the stability and efficacy of the encapsulated fish oil. The researchalso emphasizes the difficulties presented by oxidation and the significance of encapsulation in preserving thenutritional value and longevity of fish oil supplements. This review aims to offer insights into using differenttypes of gelatins for encapsulating fish oil to enhance its oxidative stability and health advantages through acomparative analysis.